2014
DOI: 10.1136/annrheumdis-2013-204924
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E-mutation is invariably present and associated to oncogene-induced senescence in Erdheim-Chester disease

Abstract: The oncogenic BRAF(V600E) mutation is present in biopsies and in the peripheral blood from all patients with ECD who were evaluated and is associated with OIS. These findings have significant implications for the pathogenesis, diagnosis and treatment of ECD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 42 publications
4
74
0
6
Order By: Relevance
“…However, the heterogeneous nature of ECD and LCH lesions frequently presents a challenge to the accurate identification of BRAFV600E mutations in lesional tissue. 8 In addition, several groups have noted that a larger proportion of LCH and ECD lesions have activation of ERK signaling than that demonstrated to have the BRAFV600E mutation. 3,8,9 Interestingly, Cangi et al recently identified that 18 of 18 ECD patients had a BRAFV600E mutation in DNA from whole lesional tissue if an ultrasensitive methodology was used, suggesting that current data underestimate the true mutational frequency of BRAFV600E mutations in ECD.…”
Section: Introductionmentioning
confidence: 99%
“…However, the heterogeneous nature of ECD and LCH lesions frequently presents a challenge to the accurate identification of BRAFV600E mutations in lesional tissue. 8 In addition, several groups have noted that a larger proportion of LCH and ECD lesions have activation of ERK signaling than that demonstrated to have the BRAFV600E mutation. 3,8,9 Interestingly, Cangi et al recently identified that 18 of 18 ECD patients had a BRAFV600E mutation in DNA from whole lesional tissue if an ultrasensitive methodology was used, suggesting that current data underestimate the true mutational frequency of BRAFV600E mutations in ECD.…”
Section: Introductionmentioning
confidence: 99%
“…20 BRAF-mutated histiocytes in ECD activate oncogeneinduced senescence, a protective mechanism against oncogenic events characterized by robust production of pro-inflammatory cytokines, including IL-6. 10,21,22 The pro-inflammatory milieu induced by senescent cells favors the recruitment and activation of histiocytes into ECD lesions. 21 The clinical response observed in Patients 1 and 2 was indeed associated with a decrease or stabilization of these mediators (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Recent evidence indicates that deregulated activation of the mitogen-activated protein kinase (MAPK) pathway due to oncogenic mutations in the BRAF, NRAS, PIK3CA, and MAP2K1 genes is central to the pathogenesis of ECD. [8][9][10] Following these discoveries, treatment with small-molecule inhibitors of BRAF V600E (vemurafenib) or MEK (cobimetinib, trametinib) came to fruition (reviewed in 11 ). However, there are several concerns regarding the safety and tolerability of long-term treatment, as these agents are often associated with severe or life-threatening adverse effects, 12 while unequivocal therapy end-points and maintenance regimens are yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] This observation and the anecdotal responses reported with the BRAF600E inhibitor, vemfurafenib, have provided the rationale for clinical testing of such pathwaydirected treatments in ECD. 8 Third, the proposed clinical classification of ECD as asymptomatic and symptomatic will be helpful in tailoring therapy according to disease severity.…”
mentioning
confidence: 99%
“…6 Mice harboring Mbnl1 2/2 plus Mbnl2 1/2 alleles also recently have been shown to exhibit cardinal features of DM muscle disease. 7 In additional contexts, extended roles of MBNLs are illustrated by regulation of FOXp1 AS in a context of ES cell pluripotency, 8 and in insulin receptor transcript AS. 6 In studies by Cheng et al,…”
mentioning
confidence: 99%